AB0719 CLINICAL FEATURES OF PATIENTS WITH ANKYLOSING SPONDYLITIS AND SECONDARY AA-AMYLOIDOSIS. (2nd June 2020) - Rumiantceva, D.; Agafonova, E.; Krasnenko, S.; Podryadnova, M.; Starkova, A.; Urumova, M.; Erdes, S.
Abstract : Background: Secondary AA-amyloidosis is one of the most serious complications of ankylosing spondylitis (AS). Better knowledge of specific to secondary AA-amyloidosis clinical features is important for improving further management of these patients. Objectives: To conduct a comparative analysis of AS patients with and without secondary AA-amyloidosis. Methods: The study included 220 AS patients (according to modified New York criteria) without amyloidosis - Group 1, and 9 AS patients with histologically confirmed secondary AA-amyloidosis – Group 2. Results: Table 1 presents the comparative characteristics of Group 1 and Group 2 patients. Both groups were comparable in terms of patients' age, rates of HLA B27 positivity, presence of enthesitis, uveitis, inflammatory bowel diseases (IBD), and psoriasis on assessment. Group 2 patients tended to be younger at AS onset, while shorter disease duration and fewer male patients were established for Group 1. Group 2 had higher rates of extra-spinal AS manifestations, such as arthritis and coxitis. It should be noted that all AS patients with secondary AA-amyloidosis were males, with clinically manifest arthritis, involving hip joints, and AS onset in the childhood in 8 out of 9 cases. Conclusion: Patients with AS and secondary AA amyloidosis are predominantly of male gender, who usually get sick in childhood, have 100% HLA-B27 positivity, peripheral arthritis, and coxitis. Disclosure of Interests: None declared